Impact of Silver Nanoparticles on Lemon Growth Performance: Insecticidal and Antifungal Activities of Essential Oils From Peels and Leaves - Mosa, Walid F. A.; Mackled, Marwa I.; Abdelsalam, Nader R.; Behiry, Said I.; Al-Askar, Abdulaziz A.; Basile, Adriana; Abdelkhalek, Ahmed; Elsharkawy, Mohsen M.; Salem, Mohamed Z. M. (Frontiers in Plant Science, 2022)
Ten-year-old lemon (Citrus limon L. cv. Eureka) was used during the 2019 and 2020 seasons to investigate the effect of AgNPs at control, 5, 7.5, and 10 mg/L as a foliar application on vegetative growth, yield, and fruit quality. The selected trees were subjected to agricultural practices applied in the field during the study. The results indicated that the foliar application of AgNPs positively improved the shoot length, total chlorophyll, flower, and fruit set percentage, fruit yield, physical and chemical characteristics of fruits, and leaf mineral composition from macro and micronutrients compared to control in both seasons. The foliar application of AgNPs at 10 mg/L showed the highest mean values followed by 7.5 and 5 mg/L, respectively, for the previous characteristics. The treated leaves and fruit peels were hydrodistillated to extract the essential oils (EOs), and GC–MS analysis of leaf EOs. The analysis of leaves EOs showed the presence of neral, geranial, neryl acetate, and limonene as the main abundant bioactive compounds. While in peel the main compounds were neral, geranial, neryl acetate, D-limonene, geraniol acetate, linalool, and citronellal. Toxin effect of both EOs from leaves and peels were evaluated on the rice weevils (Sitophilus oryzae) and the results indicated a higher effect of lemon peel EOs than leaves based on mortality percentage and the values of LC50 and LC95 mg/L. Melia azedarach wood samples loaded with the produced lemon EOs were evaluated for their antifungal activity against the molecularly identified fungus, Fusarium solani (acc # OL410542). The reduction in mycelial growth was increased gradually with the applied treatments. The most potent activity was found in lemon leaf EOs, while peel EOs showed the lowest reduction values. The mycelial growth reduction percentages reached 72.96 and 52.59%, by 0.1% leaf and peel EOs, respectively, compared with control.